The impact of COVID-19 on the mental health of radiography staff and managers in Northern Ireland, UK: The radiography managers' perspective. (October 2022) - Flood, T.; McFadden, S.; Shepherd, P.
Abstract: Introduction: Increasing evidence suggests that the COVID-19 pandemic has influenced the mental health of health professionals, including radiographers. Less is known about the effect of the pandemic on the mental health of radiography managers. Radiography managers have led their teams through the pandemic, making unpopular decisions to safeguard staff and patients. This study explores radiography managers' perceptions regarding the impact of the COVID-19 pandemic on the mental health of themselves and their staff. Methods: Ethical approval was obtained from the NHS Research Ethics Committee (ID 287032). Eleven interviews were conducted with therapeutic and diagnostic radiography managers between March–April 2021. Written information was also included from a paediatric diagnostic radiography manager. Data was analysed independently by 2 researchers using thematic analysis. Results: Three central themes emerged: 1) Factors perceived to have negatively influenced mental health, which included changing PPE guidance, restructuring of work conditions, social isolation, challenges to patient care and lack of quality vacation leave. 2) Factors perceived to have positively influenced mental health, which included witnessing staff resilience and team camaraderie. 3) Support provided for mental health. Conclusion: Managers felt that they had implemented appropriate strategies to support their staff throughout the first year of the pandemic and expressed feeling responsible for the wellbeing of their staff. Strong empathy was evident towards staff and their experiences. Despite the availability of mental health support services, managers felt that resources were underutilised by radiography teams. Implications for practice: Managers should be proactive in communicating their appreciation for their staff in an era where remote working can add to disconnect between staff and management. Mental health support services should be promoted and continually reviewed, to ensure that appropriate support services are maintained.